2014
DOI: 10.1002/2013gl059180
|View full text |Cite
|
Sign up to set email alerts
|

Photographic observations of streamers and steps in a cloud‐to‐air negative leader

Abstract: A color photograph has been obtained of a negative lightning leader in clear air at 10.3 km altitude. The individual leader steps are resolved as relatively straight segments of at least ~200 m in length, between sharp kinks (nodes) in the channel. Each node is accompanied by a group of streamers of ~100 m in length. One node has an unconnected secondary leader with streamers at both ends. Lightning Mapping Array observations show that the leader was part of an intracloud (IC) flash. The observation shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 22 publications
8
46
2
1
Order By: Relevance
“…Edens et al . [] observed cloud‐to‐air leaders in two IC flashes with a digital still camera and the LMA. They reported that the step lengths were at least 200 m and 264 m, respectively, in two leaders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Edens et al . [] observed cloud‐to‐air leaders in two IC flashes with a digital still camera and the LMA. They reported that the step lengths were at least 200 m and 264 m, respectively, in two leaders.…”
Section: Resultsmentioning
confidence: 99%
“…If this is true, the difference in the rate of radio emissions from IC and CG flashes cannot be simply attributed to the difference in step length in different altitudes as in Edens et al . []. Instead, we think that the ambient electric field is a more important factor, which will be discussed below along with other parameters in Table .…”
Section: Discussionmentioning
confidence: 99%
“…This step was relatively straight and had a 2‐D length of about 1 km. (For comparison, Edens et al, , reported negative‐leader step lengths in excess of 200 m near 10‐km altitude and Pilkey, , Figures A‐1 and A‐2, reported what appeared to be a space leader initiated about 84 m from the positive leader channel near 3‐km altitude and 364 μs later connected to the lateral surface of that channel.) It appeared to occur in virgin air, propagated at a remarkably high effective speed of the order of 10 6 m/s, and produced a streamer corona burst at its far end.…”
Section: Discussionmentioning
confidence: 97%
“…The brush‐like streamer zone at the step tip was observed for upward negative leaders by Berger (), and a faint luminosity at the lower end of bright steps was reported by Schonland et al () for one downward stepped leader. Edens et al () presented optical records showing negative leader steps near 10‐km altitude. The step lengths were about 200 m or more; that is, considerably longer than at lower altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Berger [1967] [27] and Idone [1992] [28] presented photographic evidences of brush-like corona extending a few meters ahead of the tips of upward negative and upward positive leaders, respectively. Recently, Biagi [29] documented streamer zones (corona brushes) at negative leader tips with spatial extents of a few meters at some tens of meters AGL (altitude triggered lightning) and 100-200 m at 10 km AGL (cloud flash), respectively. The corona-like formations hypothesized in this paper, occurring at an altitude of 3.2 km AGL, were estimated to have 100-200 m spatial extent.…”
Section: F Discussionmentioning
confidence: 99%